Experimental investigation of seawater cooling during severe accidents in a nuclear reactor - Ahmed, Zayed (Kansas State University, 2022)
During the Fukushima Daichii nuclear accident, seawater was injected into the reactor core to cool the decay heat generated from the nuclear fuel elements. The impact of dissolved salts in water on the coolability is not well understood, especially on the heat generating porous debris bed, that is expected to form in severe accident scenarios. Under the boiling conditions with seawater, the presence of dissolved salts is expected to impact the heat transfer and hydrodynamic characteristics of the cooling process. The focus of this experimental work is to measure the differences in the cooling performance between seawater and pure water in two geometries - an annulus and an emulated debris bed. Insights from experiments on the annular test section inform the heat transfer degradation of using seawater under different scenarios. The contribution of the boiling mechanism to the total heat removal rate is quantified through high speed image analysis. The experimental setup designed to study debris bed coolability through high spatial resolution temperature measurements and novel void fraction measurements is discussed. The sustainable cooling of the porous debris bed using emergency cooling water requires the continuous supply of coolant to all regions within the bed to prevent a dryout. This dryout is measured using Distributed Temperature Sensing (DTS) and pressure drop measurements and the heat flux at which dryout occurs is quantified at various parameters and salt concentrations. An increase in coolability was observed to occur with an increase in the dissolved salt concentration. First of a kind, non-intrusive void fraction measurements were performed inside the debris bed by utilizing thermal neutrons of the KSU Triga Mark II nuclear reactor. The classical models for estimating the void fraction inside the boiling debris bed were validated for the first time ever. This study gives modelers high fidelity temperature and void fraction data for model validation. From a reactor safety point of view, this work suggests that using seawater has short term cooling benefits by enhancing the dryout heat flux, but longterm cooling can be limited due to the plugging of pores, which can cause further progression of an accident.
Keywords: Debris bed; Seawater; Boiling; Neutron imaging